Evaluating the Link between Consumers' Savings Portfolio Decisions, their Inflation Expectations and Economic News - Eva Arnold; Lena Dräger; Ulrich Fritsche (Hamburg University, Department Socioeconomics, 2014)
Utilizing the microdata from a first cross-section of a new household survey at the University of Hamburg, we analyse if consumers respond to their own inflation expectations and economic news that they have observed recently when they plan to adjust their savings portfolio in the next year. We extract three factors to control for consumers' socio-demographic and personality characteristics. Our estimates from the socio-demographic factors suggest that high education and personal income matter most for a planned savings portfolio adjustment. Interestingly, higher inflation expectations only affect planned savings adjustments due to higher interest rates, suggesting that consumers have a Taylor-rule-type relation in mind. Disentangling the effects of economic news, we find that news on higher inflation lead consumers to consider protection against inflation, safety of the portfolio and higher interest rates as reasons for a savings adjustment. In addition positive news on the business cycle and on the Euro crisis increase the likelihood that consumers consider a savings adjustment to protect against inflation or due to higher expected interest rates, respectively. Overall, it seems that economic news observed are incorporated into decisions regarding a planned savings portfolio adjustment, while inflation expectations play an indirect role.
Keywords: C21; D14; D84; 330; Consumers' savings adjustment; inflation expectations; economic news; survey microdata